Deformation Characteristics of a Deep Subway Foundation Pit in Hard Rock Strata under a Delayed Supporting Condition - Li, Yang; Ma, Zhanguo; Gao, Furong; Gong, Peng; Gong, Zhiqun; Li, Kelong (Shock and Vibration, 2023)
In this investigation, deformations of a deep foundation pit in hard rock strata, respectively, under delayed and in-time supporting schemes of one-layer transverse reinforced concrete bracings at the top of the foundation pit, one-layer steel bracings at a depth of 8 m, and one-layer prestressed anchorages at a depth of 22.5 m during excavation were characterized according to lateral deformations of the foundation pit, settlements of the surrounding ground, and axial forces of the steel bracings according to numerical calculations and on-site monitoring. Numerical calculation results showed that the maximum lateral deformations of the foundation pit and settlements of the surrounding ground were, respectively, 10.34 mm and 8.49 mm at an excavation depth of 31 m, which were obviously larger than those under in-time supporting. Meanwhile, under delayed supporting conditions, lateral deformations of the foundation pit and settlements of the surrounding ground were far less than the allowed values, respectively, being 0.3% and 0.15% of the excavation depth, required in the Chinese standard of GB50007-2011, indicating that the foundation pit under delayed supporting conditions had good stability. Therefore, when excavating deep foundation pits in hard rock strata, proper delayed supporting schemes could be considered so that strengths of the surrounding hard rocks could be utilized to the fullest, and at the same time, more spaces for excavation could be freed up, and construction duration and construction costs could thus be lowered.